Reciprocal regulation of pro-inflammatory annexin A2 with estrogen in the progression of postmenopausal osteoporosis - Rohan Raj, Vinay Kumar C, Vikram Shetty, Vijaykrishnaraj M, Praveenkumar Shetty, Prakash Patil (Journal of Applied Pharmaceutical Science, 2024)
Osteoporosis is a systemic condition where there is a decrease in bone mineral density (BMD) increasing the fragility of the bone, which in turn increases the risk of fracture. Osteoclasts express Annexin A2 (ANXA2), a calcium-dependent phospholipid-binding protein that, when overexpressed, promotes osteoclastic activity. This study aims to confirm the role of proinflammatory ANXA2 in bone remodeling and determines its association with estrogen expression causing low bone density in postmenopausal women. After obtaining the consent, pre and postmenopausal women participants (n = 42) were subjected to Dual-energy X-ray absorptiometry (DXA scan). Later, serum estradiol (E2) was analyzed using an automated hematology analyzer, and serum ANXA2 levels were determined by ELISA according to the manufacturer’s instructions. The osteoporotic post-menopausal women (58.6 ± 9.2 years) have lower BMD (0.7 ± 0.2 g/cm2) with a very low T-score (DXA score) of –3.32 ± 1.42, compared to pre-menopausal (25.34 ± 6.03 years) having higher BMD (0.97 ± 0.17 g/cm2) with a T score of –0.79 ± 1.01. Furthermore, the serum estradiol levels were significantly (p < 0.001) lower in post-menopausal women (5.52 ± 1.35 pg/ml) compared to pre-menopausal women (90.18 ± 52.76 pg/ml). Conversely, the ANXA2 levels were significantly (p < 0.001) higher among post-menopausal women (76.4 ± 10.07 ng/ml) compared to pre-menopausal women (62.97 ± 7.11 ng/ml). This study concludes that the serum ANXA2 levels in post-menopausal individuals with osteoporosis are inversely related to hip BMD but have very poor levels of serum estrogen. Therefore, the greater levels of ANXA2 have a role in promoting osteoclastogenesis linked to osteoporosis.
Keywords: Annexin A2, bone mineral density (BMD), estradiol (E2), osteoporosis, post-menopausal women